Convection Enhanced Delivery for Diffuse Intrinsic Pontine Glioma: Review of a Single Institution Experience - Umberto Tosi; Mark Souweidane (MDPI AG, 2020)
Diffuse intrinsic pontine gliomas (DIPGs) are a pontine subtype of diffuse midline gliomas (DMGs), primary central nervous system (CNS) tumors of childhood that carry a terrible prognosis. Because of the highly infiltrative growth pattern and the anatomical position, cytoreductive surgery is not an option. An initial response to radiation therapy is invariably followed by recurrence; mortality occurs approximately 11 months after diagnosis. The development of novel therapeutics with great preclinical promise has been hindered by the tightly regulated blood-brain barrier (BBB), which segregates the tumor comportment from the systemic circulation. One possible solution to this obstacle is the use of convection enhanced delivery (CED), a local delivery strategy that bypasses the BBB by direct infusion into the tumor through a small caliber cannula. We have recently shown CED to be safe in children with DIPG (NCT01502917). In this review, we discuss our experience with CED, its advantages, and technical advancements that are occurring in the field. We also highlight hurdles that will likely need to be overcome in demonstrating clinical benefit with this therapeutic strategy.